Digital twins for trans people in healthcare: queer, phenomenological and bioethical considerations - Quiñones, Jose Luis Guerrero (Journal of medical ethics, 2025)
Healthcare is one of the domains in which artificial intelligence (AI) is already having a major impact. Of interest is the idea of the digital twin (DT), an AI-powered technology that generates a real-time representation of the patient's body, offering the possibility of more personalised care. Our main thesis in this paper is that the DT does not merely represent the patient’s body but produces a specific body. We argue, from a philosophical perspective and an ethical-phenomenological approach, that the virtual body created by the DT has a major impact on one's self-understanding, having consequences for gender expression and identification, and for health. This has deep implications for people who do not conform to gender normativity, for example, trans individuals. We advocate that, with thoughtful development, DT technology can and should be empowering, contributing to better addressing the diversity of bodies and facilitating trans people’s experience in healthcare contexts.